Bounded set of economic uncertainty and robust viability: An illustration from farming systems. (14th July 2018) - Bates, Samuel; Angeon, Valérie; Désilles, Anna; Saint‐Pierre, Patrick
Abstract : Abstract: Uncertainty occupies a major place in the literature, both when it is being defined and when it is being measured. The mathematical viability theory framework provides useful concepts to go beyond the probabilistic views of uncertainty that are not able to capture all forms of uncertainty, particularly in the absence of statistical regularities. Bounded‐set uncertainty can help to analyze changes in the evolutionary conditions that affect ecological and social systems with probabilistic or nonprobabilistic distributions. This paper introduces uncertainty into a viability model by associating stochastic and bounded‐set uncertainty related to sales price as a driver of economic uncertainty. Based on an illustration of agroecosystems, the model identifies decision rules that guarantee viability. The larger the initial crop portfolio for sequential diversification is, the lower the costs to belong to the viability kernels will be, regardless of economic and environmental constraints. The diversification of farming systems transforms their complexity into an advantage against uncertainty, which opens up numerous viability trajectories. Recommedations for Resource Managers: Considering the relevance of a bounded set of economic uncertainty, restoring soil quality and choosing diversification guarantee viability and allow a single generation of farmers to relax both their environmental and economic constraints. When the time available to conform to both their environmental and economic constraints decreases, sequential diversification can be used as a tool to relax the economic constraint of self‐financing soil restoration. Sequential diversification is an asset, especially for low‐quality soil. Even under uncertainty and very low soil quality, diversification drastically reduces the value‐at‐risk for viable farming investment. Eligibility for agricultural subsidies should be conditional on soil quality to motivate practices of soil restoration that provide a sort of insurance against economic uncertainty.